Past, present, and future of pro-environmental behavior in tourism and hospitality: a text-mining approach - Loureiro, S. M. C.; Guerreiro, J.; Han, H. (Journal of Sustainable Tourism, 2022)
Scholars have been interested in examining what drives pro-environmental behavior. However, only a few scientific studies have been devoted to analyzing and understanding the pro-environmental behavior of those that are on vacation. Therefore, the current paper contributes to the existing literature by employing a text-mining approach to conduct a full-text analysis of 210 articles and (1) describes pro-environmental conceptualization, (2) presents the important topics and studies that have emerged from the literature, and (3) suggests directions for future research. The eight core topics that were uncovered contributed to discussion of the content of publications, related theories, core constructs, methodologies, main authors, and journals. The paper shows that the literature on pro-environmental behavior uses more quantitative than qualitative approaches and uses structural equations or regression analysis to explore the data. The findings also show that researchers tend to employ well-known theories arising from psychology, sociology, and biology.